2012
DOI: 10.1371/journal.pcbi.1002338
|View full text |Cite
|
Sign up to set email alerts
|

Macro-level Modeling of the Response of C. elegans Reproduction to Chronic Heat Stress

Abstract: A major goal of systems biology is to understand how organism-level behavior arises from a myriad of molecular interactions. Often this involves complex sets of rules describing interactions among a large number of components. As an alternative, we have developed a simple, macro-level model to describe how chronic temperature stress affects reproduction in C. elegans. Our approach uses fundamental engineering principles, together with a limited set of experimentally derived facts, and provides quantitatively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 79 publications
3
45
1
Order By: Relevance
“…This is in line with previous studies demonstrating that C. elegans fecundity is highest at 20 °C and declines with increasing temperature (e.g. Byerly et al 1976;McMullen et al 2012;Petrella 2014, but see Zhang et al 2015). The decrease of reproductive function at high temperatures seems to be associated with functioning of both spermathogenic and oogenic germ lines (Aprison and Ruvinsky 2014;Petrella 2014), although the relative contribution of these two factors varies between strains (Petrella 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with previous studies demonstrating that C. elegans fecundity is highest at 20 °C and declines with increasing temperature (e.g. Byerly et al 1976;McMullen et al 2012;Petrella 2014, but see Zhang et al 2015). The decrease of reproductive function at high temperatures seems to be associated with functioning of both spermathogenic and oogenic germ lines (Aprison and Ruvinsky 2014;Petrella 2014), although the relative contribution of these two factors varies between strains (Petrella 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, it has been shown that increased temperature affects sperm and oocyte production, ovulation and spermatid activation in C. elegans (Aprison and Ruvinsky 2014;Petrella 2014). We might also expect thermal stress to result in elevated gamete death (McMullen et al 2012) as increased temperature during ovulation has been shown to reduce gamete viability in some fish species (Pankhurst and Van Der Kraak 1997). However, low incidence of sterility in selfing lines proves that both types of gametes successfully function in hermaphrodites under the same thermal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The time between the molt that produces the adult stage of C. elegans and the onset of egg laying is about nine hours at 20 ° C [20], [21]. During that time period, while continuing to grow, hermaphrodite worms cease producing sperm, begin producing oocytes, begin ovulation, spermatids mature and become sperm, fertilization commences, and the first egg is laid [44].…”
Section: Methodsmentioning
confidence: 99%
“…This is primarily controlled by the master regulator of the HSR, which in eukaryotes is heat shock transcription factor HSF-1. HSF-1 functions as a rheostat for acute stress, to prevent cell death, and monitors chronic proteotoxic stress that affects fecundity and lifespan (Abravaya et al, 1991;Morley and Morimoto, 2004;Åkerfelt et al, 2010;Lindquist and Kelly, 2011;McMullen et al, 2012). HSF-1 is a highly conserved member of the HSF gene family that is constitutively expressed and negatively regulated in most cell types in the absence of stress (Åkerfelt et al, 2010).…”
Section: Maintaining Proteome Integrity By Cellular Stress Responses mentioning
confidence: 99%